Optimazion Analysis of Temperature and Fermentation Controlled Chamber (TFCC) with Hybrid System to Control Fermentation on Tape - Rofi'i, Ahmad; Purnomo, Fendik Eko; Afriansyah, Faisal Luthfi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The aim of this research is to determine analysis for optimizing tape fermentation using a Temperature and Fermentation Controlled Chamber (TFCC) with a Hybrid System. The resulting numerical model was analyzed using a non-linear differential method using Runge-Kutta. The thing that was analyzed was the change in the rate of yeast concentration, the rate of change in the concentration of ethanol and glucose resulting from the fermentation process. TFCC with Hybrid System Technology is equipped with an automated system accompanied by sensors that detect food quality and can be directly observed through the LCD screen integrated in the device. The research method used is experimental research by designing a tool that can be used to produce/cook fermented foods while monitoring pH, alcohol, glucose levels and temperature levels which are integrated in a set of tools called the TFCC with Hybrid Systems Technology . From the numerical explanation, it can be seen that when t is small, the rate of yeast development in the fermentation process will be small, the number of yeast cells is still small. As a result, the growth rate will be slow. This can be seen from the graph of the increase in X(t) and P(t) as well as the graph of S(t) which is still slow. The greater the time t, the rate of yeast consumption is also greater because the number of yeast cells is also increasing. As a result, the growth rate of ethanol and sugar is also large. This can be seen from the graph of an increase in X(t) and P(t) as well as a graph of a faster decline in S(t). When the maximum consumption rate is reached, then the values of X(t), S(t) and P(t) are constant. The amount of concentration in the resulting ethanol is close to the initial concentration of sugar produced.